2019
DOI: 10.1111/bjd.17796
|View full text |Cite
|
Sign up to set email alerts
|

DSP mutations and arrhythmogenic cardiomyopathy

Abstract: Summary Arrhythmogenic Cardiomyopathy (AC) is a relatively rare inherited disorder of the heart muscle and can lead to sudden death in patients, often under 35 years of age. AC can be very difficult for doctors to diagnose because the initial symptoms are often subtle so they can go unnoticed. In a rare form of AC, affected patients also have striking curly hair and abnormally thickened skin on the palms and soles. This can make the diagnosis easier to make. This study, from London, UK, looked at families with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent systematic evaluation of cutaneous abnormalities among DSPtv showed all patients expressed some degree of skin or hair abnormalities, except those with DSPtv in the nonconstitutive NMD-competent region (cardiac isoform, DSPI). 32 Interestingly, we report 1 proband and their affected relative with palmoplantar keratoderma, with a DSPtv in the nonconstitutive NMD-competent region. Another study reported 10% of DSPtv had cutaneous disease only, while 12% were reported to have LV dominant ACM and cutaneous disease.…”
Section: Discussionmentioning
confidence: 81%
“…A recent systematic evaluation of cutaneous abnormalities among DSPtv showed all patients expressed some degree of skin or hair abnormalities, except those with DSPtv in the nonconstitutive NMD-competent region (cardiac isoform, DSPI). 32 Interestingly, we report 1 proband and their affected relative with palmoplantar keratoderma, with a DSPtv in the nonconstitutive NMD-competent region. Another study reported 10% of DSPtv had cutaneous disease only, while 12% were reported to have LV dominant ACM and cutaneous disease.…”
Section: Discussionmentioning
confidence: 81%